New coconut opportunities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In September 2000, the FAO received its first patent ever, for a cold sterilisation method to produce fresh coconut drink (see Spore 80, p 7). The United Kingdom has granted the patent already to FAO, and Japan and Canada should follow soon. FAO is...